In-Depth X-Ray Photoelectron Spectroscopy of Resistive Switching Devices - Narciso, Gonçalo Filipe Fernandes (2019)
This work has explored the possibility of using x-ray photoelectron spectroscopy (XPS), for studying the chemical properties (i.e. atomic ratios and oxidation states) of several metal-insulator-metal (MIM) structures. This thesis aims to better understand the operation mechanism that imposes a reversible change in the resistance state of the studied devices. Three different configurations (ITO/ZTO*/Pt, Pt/ZTO/Ti-Au, ITO/GIO*/Au) were fabricated following a physical vapour deposition methodology and patterned using shadow masks, specifically designed for this purpose. An electrical characterization was performed first, to evaluate the uniformity between the devices through the study of their pristine state and second, to change the resistance state, applying a high voltage signal, followed by an in-depth XPS analysis. The XPS argon cluster depth profiling of the produced MIM structures showed that the resistive switching mechanism of the Pt/ZTO/Ti-Au device was not ionic, since no change of cation ratios and oxidation states were observed throughout the depth of the device, comparing pristine state and the low resistive state (LRS). The ITO/GIO/Au device exhibited area-dependent electroforming, which led to an irreversible change in the forward direction. Remarkably, the diode was free of any hysteresis after electroforming. The XPS depth profile revealed an increased indium concentration within the bulk region near the ITO after electroforming, compared to the pristine state of the device. Hence, despite being irreversible, the resistance change of the device is clearly related to an ionic mechanism. *ZTO: zinc-tin oxide; GIO: gallium-indium oxide